Membangun Kesadaran Legalitas Usaha Melalui Pendampingan Pembuatan Nomor Induk Berusaha (Nib) Bagi Usaha Mikro, Kecil dan Menengah (Umkm) Dusun Sumber Cangkelek, Desa Wangkal, Kecamatan Gading, Kabupaten Probolinggo - Hazimah Iskarimah, Ima; I’tisoma Billah, Zahida (Najah: Journal of Research and Community Service, 2025)
The Community Service Program (PKM) aims to analyze the role of community service in priority communities and the influence of innovation internalization and external environmental changes on efforts to improve the performance of micro, small, and medium enterprises (MSMEs). One very important aspect in the development of MSMEs is business legality. The objective of this community service program is to provide assistance to MSME actors in Sumber Cangkelek Hamlet, Wangkal Village, Gading Subdistrict in creating accounts and obtaining business licenses directly at the Public Service Mall and obtaining business legality, in this case in the form of a business identification number (NIB). The community service activity carried out by group 29 of UNZAH's KKN PKM was due to the lack of enthusiasm among micro, small, and medium entrepreneurs in Sumber Cangkelek Hamlet, Wangkal Village, Gading Subdistrict in obtaining a Business Identification Number (NIB). NIB is a business identification number used by business actors to obtain business licenses and commercial or operational permits. One of the economic assets that is still underdeveloped in Sumber Cangkelek Hamlet is micro, small, and medium enterprises (MSMEs). This PKM activity uses the ABCD (Asset-Based Community Development) Approach, which consists of 6 stages, namely: a) Discovery Stage, b) Dream Stage, c) Design Stage, d) Destiny Stage, e) Define Stage, and f) Reflection Stage in data collection, resulting in the collection of 12 MSMEs in Wangkal Village, Gading District, spread across several hamlets, namely Krajan Hamlet, Sumber Cangkelek Hamlet, and Kramat Hamlet. The result of this community service activity was the issuance of Business Identification Numbers (NIB) for two MSME actors in Sumber Cangkelek Hamlet, Wangkal Village, Gading District.